Chemically Functionalized Natural Cellulose Materials for Effective Triboelectric Nanogenerator Development. (16th June 2017) - Yao, Chunhua; Yin, Xin; Yu, Yanhao; Cai, Zhiyong; Wang, Xudong
Abstract : Cellulose, the most abundant natural polymer, is renewable, biodegradable, and cost competitive. This paper reports the development of a high‐performance triboelectric nanogenerator (TENG) with both contacting materials made from cellulosic materials. Cellulose nanofibrils (CNFs) are used as the raw material, and chemical reaction approaches are employed to attach nitro groups and methyl groups to cellulose molecules to change the tribopolarities of CNF, which in turn significantly enhances the triboelectric output. Specifically, the nitro‐CNF possesses a negative surface charge density of 85.8 µC m −2, while the methyl‐CNF possesses a positive surface charge density of 62.5 µC m −2, reaching 71% and 52% of that for fluorinated ethylene propylene (FEP), respectively. The figure of merit of the nitro‐CNF and methyl‐CNF is quantified to be 0.504 and 0.267, respectively, comparable to or exceeding a number of common synthetic polymers, such as Kapton, polyvinylidene fluoride, and polyethylene. The TENG fabricated from nitro‐CNF paired with methyl‐CNF demonstrates an average voltage output of 8 V and current output of 9 µA, which approaches the same level obtained from TENG made from FEP. This work demonstrates a successful strategy of using environmentally friendly, abundant cellulosic materials for replacing the synthetic polymers in TENG development. Abstract : Cellulose nanofibrils (CNFs) are chemically functionalized with nitro groups and methyl groups to engineer their tribopolarities, which in turn significantly enhances the electrical output of the triboelectric nanogenerator. The figures of merit of the nitro‐CNF and methyl‐CNF are quantified to be 0.51 and 0.28, respectively, comparable to or exceeding a number of common synthetic triboelectric polymer materials.